2014
DOI: 10.1155/2014/510846
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Antitumor Effect of the IL-12 Gene Therapy and the Expression of Th1 Cytokines in an HPV16-Positive Murine Tumor Model

Abstract: Objective. The goal of the present study was to investigate the effect of IL-12 expressed in plasmid on the Th1 cytokine profile in an experimental HPV16-positive murine tumor model and the association with the IL-12's antitumor effect. Methods. Mice were injected with BMK-16/myc cells to establish HPV16-positive tumor and then pNGVL3-mIL-12 plasmid; pcDNA3 plasmid or PBS was injected directly into tumor site. The antitumor effect of the treatment was evaluated and the cytokines expression profile in each tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Such NP‐mediated inhibition of self‐activation may have triggered the increased release of IL‐12 via NF‐κB and STAT3 downregulation (downregulation > switch of M2 towards M1 > reduced IL‐10 levels > inhibition of M2 autocrine activation by IL‐10 > high levels of IL‐12). IL‐12 is an important Th1 immune response mediator that exerts anti‐tumour activity through increased proliferation, survival, and/or cytotoxicity of NK cells, CD8, and CD4 T cells, as well as suppression of T reg activity (Garcia Paz et al, 2014; Zagozdzon & Lasek, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Such NP‐mediated inhibition of self‐activation may have triggered the increased release of IL‐12 via NF‐κB and STAT3 downregulation (downregulation > switch of M2 towards M1 > reduced IL‐10 levels > inhibition of M2 autocrine activation by IL‐10 > high levels of IL‐12). IL‐12 is an important Th1 immune response mediator that exerts anti‐tumour activity through increased proliferation, survival, and/or cytotoxicity of NK cells, CD8, and CD4 T cells, as well as suppression of T reg activity (Garcia Paz et al, 2014; Zagozdzon & Lasek, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF and IL-12 have been identified as promising cytokines for cancer immunotherapy, including treatment of melanoma; these cytokines activate antitumor immune cells and expand IFN- γ signaling through a positive-feedback loop. 4649 …”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently revealed the association of inflammatory levels with survival of tobacco exposed prostate cancer patients . It has been demonstrated that IL‐18 exerts anti‐tumor effects which are mediated by apoptosis induction and angiogenesis inhibition . Few other in vivo reports have also shown that IL‐18 has potent anti‐tumor effects when administered in animal models of lung cancer, lymphoma and melanoma .…”
Section: Discussionmentioning
confidence: 99%